Bizarre Chorionic-type Trophoblast in Second-trimester and Third-trimester Placentas: Clinicopathologic Characterization of a Placental Pseudoneoplastic Lesion. (February 2022) - Murdock, Tricia A.; Varghese, Aaron; Xing, Deyin; Schoolmeester, J. Kenneth; Alexander, Caitlin; Baergen, Rebecca N.; Dahoud, Wissam; Hopkins, Mark R.; Askin, Frederic; Vang, Russell
Abstract : Bizarre (atypical/symplastic) cells have been described in various gynecologic normal tissues and benign neoplasms. This type of bizarre cytologic change is usually an incidental finding and is regarded as a benign process. We describe 17 cases of bizarre chorionic-type trophoblast in second-trimester and third-trimester placentas that created concern for an underlying/undersampled or incipient intraplacental trophoblastic neoplasm, predominantly found in intervillous trophoblastic islands (11/17), placental septae (6/17), chorionic plate (1/17), and/or the chorion layer of fetal membranes (2/17). The bizarre trophoblastic cells exhibited sheet-like or nested architecture, had a multifocal/patchy distribution, and/or were present as individual cells within hyaline stroma; they were characterized by large nuclei with smudgy chromatin and occasional intranuclear pseudoinclusions. The degree of atypia was classified as mild (0/17), moderate (3/17), or severe (14/17). Mitotic figures and necrosis were not identified. A dual immunohistochemical stain for trophoblast (hydroxyl-delta-5-steroid dehydrogenase) and a proliferation marker (Ki-67), performed in 15 cases, demonstrated 0% to very low proliferative activity within the bizarre trophoblast (0% to 2% [10/15], 3% to 8% [5/15]). Immunohistochemical stains for fumarate hydratase showed intact/retained expression in the bizarre cells in 7 of 7 cases. Clinical follow-up ranged from 1 to 45 months, and all patients were alive and well without subsequent evidence of a gestational trophoblastic or other neoplasms. We conclude that bizarre chorionic-type trophoblast in second-trimester or third-trimester placentas have the potential to mimic an intraplacental trophoblastic neoplasm but are likely a benign degenerative change. This study expands the spectrum of bizarre cells that occur in the gynecologic tract.